Blockage of S100A8/A9 ameliorates septic nephropathy in mice - Wei Shi; Tian-Tian Wan; Hui-Hua Li; Shu-Bin Guo (Frontiers Media S.A., 2023)
Septic acute kidney injury (AKI) is the commonest cause of complication of sepsis in intensive care units, but its pathophysiology remains unclear. Calprotectin (S100A8/A9), which is a damage-associated molecular patterns (DAMPs) molecule, exerts a critical role in modulating leukocyte recruitment and inflammatory response during various diseases. However, role of S100A8/A9 in septic AKI is largely unknown. In this research, Septic AKI was triggered by cecal ligation and puncture (CLP) operation in wild-type mice, which treated with or without an S100A9 inhibitor, Paquinimod (Paq, 10 mg/kg) that prevents S100A8/A9 to bind to Toll-like receptor 4 (TLR4). Renal function, pathological changes, cell death, and oxidative stress were evaluated. Our research indicated that the mRNA and protein expression of S100A9 are time-dependently elevated in the kidney following CLP. Moreover, the administration of Paq for 24 h significantly improved CLP-induced renal dysfunction and pathological alterations compared with vehicle treatment in mice. These beneficial effects were associated with the inhibition of CLP-triggered renal tubular epithelial cell apoptosis, inflammation, superoxide production, and mitochondrial dynamic imbalance. What's more, we further confirmed the above findings by cell co-culture experiments. Our study demonstrates that S100A9 is a prominent protein to lead to septic AKI, and the selective inhibition of S100A9 could represent a new therapeutic approach which can treat septic AKI.